In-situ calibration for temperature-sensitive-paint heat-flux measurement on a finite base. (September 2019) - Liu, Tianshu; Risius, Steffen
Highlights: The in-situ calibration method for temperature-sensitive-paint (TSP) heat-flux measurements is developed by using the data obtained with a heat-flux sensor based on the analytical inverse heat transfer solution. The developed in-situ calibration method is used in TSP measurements in a high-enthalpy shock tube. The proposed method is useful for TSP measurements in various facilities. Abstract: This work incorporates in-situ calibration into the analytical inverse heat transfer solution for a finite base in temperature-sensitive-paint (TSP) measurements in high-enthalpy short-duration hypersonic wind tunnels. The thermal penetration parameter of the polymer layer (TSP) in the analytical inverse solution is determined by in-situ calibration based on the data obtained using a reliable heat flux sensor at a reference location. This method is applied to TSP images obtained on a wedge in a high-enthalpy shock tunnel.